Longitudinal training models for entrusting students with independent patient care?: A systematic review. Issue 2 (13th September 2021) - Bonnie, Linda H. A.; Cremers, Gaston R.; Nasori, Mana; Kramer, Anneke W. M.; van Dijk, Nynke
Abstract: Objective: The participation of students from both undergraduate medical education (UGME) and postgraduate medical education (PGME) in independent patient care contributes to the development of knowledge, skills and the professional identity of students. A continuing collaboration between students and their preceptor might contribute to opportunities for students to independently provide patient care. In this systematic review, we aim to evaluate whether longitudinal training models facilitate the independent practice of students and what characteristics of longitudinal training models contribute to this process. Method: This systematic review was performed according to the PRISMA guidelines. In May 2020, we performed a search in three databases. Articles evaluating the impact of longitudinal training models on the independent practice of students from both UGME and PGME programmes were eligible for the study. A total of 68 articles were included in the study. Quality of the included studies was assessed using the Quality Assessment Tool for Studies with Diverse Designs (QATSDD). Results: Both UGME and PGME students in longitudinal training models are more frequently allowed to provide patient care independently when compared with their block model peers, and they also feel better prepared for independent practice at the end of their training programme. Several factors related to longitudinal training models stimulate opportunities for students to work independently. The most important factors in this process are the longitudinal relationships with preceptors and with the health care team. Conclusion: Due to the ongoing collaboration between students and their preceptor, they develop an intensive and supportive mutual relationship, allowing for the development of a safe learning environment. As a result, the professional development of students is fostered, and students gradually become part of the health care team, allowing them the opportunity to engage in independent patient care. Abstract : This work demonstrates how longitudinal rotation models can make an important contribution to the entrustment of patient care to students.